Foreign direct investment, absorptive capacity and technological innovation: empirical evidence in developing economies - Mohamad, Asuantri; Mhd Bani, Nor Yasmin (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
This study investigates the impact of high inflows of FDI and absorptive capacity on technological innovations in developing economies. Utilizing panel data from 1997-2014 for a sample of 39 developing countries and applying the System-GMM estimator, we reached important conclusions. The estimated results show that FDI and absorptive capacity do not have significant effect on technological innovation when estimated separately. However, the effect changes when we consider the interaction of the variables. This indicates that FDI inflows induce technological innovation in the country with an adequate level of absorptive capacity. The results also imply that both FDI inflows and absorptive capacity are necessary in order to increase technological innovations in the host developing countries.